THE COMPARISON OF BLUE CARBON CREDIT REGULATIONS AND IMPLEMENTATION IN INDONESIA, KENYA, MADAGASCAR, AND AUSTRALIA - Rahmah Salsabilla; Afanin Fariq Fajriya; Rachma Ananda Sulaiman (Faculty of Law-Universitas Bandar Lampung, 2025)
Global climate change has become an increasingly urgent environmental issue, driven in part by the continuous degradation of forest ecosystems worldwide. Forests, which function as major global carbon sinks, are frequently converted for economic and social purposes, resulting in declining forest cover and rising carbon emissions. This situation highlights the necessity of innovative approaches to address climate-related challenges, including the conservation and enhancement of Blue Carbon Ecosystems (BCE). BCEs, particularly mangrove forests and seagrass meadows, hold substantial potential for carbon sequestration and can support environmental, social, and economic objectives when managed effectively. One mechanism developed to utilize this potential is Blue Carbon Credits (BCC). However, despite Indonesia’s vast coastal resources and high blue carbon capacity, the implementation of BCC remains underdeveloped. This study aims to examine the regulatory framework and practical progress of BCC initiatives in Indonesia and compare them with experiences from other countries. A qualitative approach was employed, using descriptive–normative analysis supported by secondary data and case studies. The findings indicate that Indonesia has significant opportunities to advance BCC initiatives, yet institutional fragmentation, overlapping authorities, and limited data integration hinder optimal implementation. Comparative insights from countries with more established blue carbon policies provide recommendations for strengthening Indonesia’s governance, improving data coordination, and enhancing the overall effectiveness of BCC implementation.